Harvesting management options for legumes intercropped in napier grass in the central highlands of Kenya - Mwangi, David Miano; Cadisch, Georg; Thorpe, W.R.; Giller, Kenneth E. (2004)
Ways of promoting integration of herbaceous forage legumes into a napier grass fodder system were evaluated with the aim of increasing forage quantity and quality on smallholder dairy farms in central Kenya. The herbaceous legumes Desmodium intortum cGreenleaf (ILRI 104), Macrotyloma axillare cAxillare (ILRI 6756 and Neonotonia wightit cTSnaroo (ILRI 9794 were intercropped with napier grass and evaluated for yield and quality (chemical composition and digestibility) of the fodder at 2 harvesting frequencies (8 and 16 weeks) and 2 cutting heights (0 and 10 cm above ground). Only D. intortum competed successfully with napier, reducing the DM yield of the grass. Due to the large forage contribution of D. intortum (15 750 kg/ha), the napier grass-D. intortum mixture had significantly higher total forage DM yield (45 910 kglha) than the mixture with N. wightii (38 840 kglha). Increasing the cutting interval from 8 to 16 weeks gave significantly higher grass DM yield but decreased N concentrations (from 11.3 to 8.9 g/kg DM and from 21.2 to 18.8 g/kg DM for napier and legumes, respecfively) and reduced legume yields. Neutral and acid detergent fibre concentrations in grass and legume tissue increased significantly as interharvesting interval increased. Cutting height did not affect the yield or quality of the grass or legumes. The proportion of legume in the forage was highest during the dry season, the napier-N wightii mixture being the poorest performer during that period. D. intortum performed consistently well and appears suitable as a companion forage legume for napier grass in central Kenya and in other areas with similar ecology.